Análise dos impactos da transformação organizacional. Do foco, da abordagem e das barreiras nos projetos transformacionais - Oliveira Júnior, João Bonifácio de (2023)
Organizational transformation is becoming increasingly complex, involving disruptive, strategic and cultural changes. Technological changes are introduced at an accelerated pace, requiring a capacity for rapid adaptation and requiring collaboration within and outside organizational boundaries, in the search for knowledge and solutions. Transformational projects are used to drive organizational renewal. The literature on organizational transformation points to a continuous and high rate of failure in transformation efforts in organizations with transformational projects. The reduced theoretical foundation contrasts with these reports of failure in organizational transformation efforts. In this study, a systematic search was conducted in the literature in order to identify patterns and support the definition of a conceptual model on transformational projects. The theoretical model constructed from the literature review was subjected to empirical validation, through a survey carried out with 187 experts. The analysis of the structural equation model showed that the transformational focus, which represents the clear and shared vision, has a significant participation in the relationship between Organizational Transformation and Transformational Project. The model contributes to practice with evidence that explains approximately 70% of the transformational project and necessary conditions for its existence, characterization and measurement, contributing to project management.